(untitled) (Bangladesh Journal of Medical Science, 2014)
Objective: Renal transplantation is frequently complicated by bacterial infections in the scenario of immunosuppression, altered metabolism and interventions resulting in prolonged morbidity. Subdued clinical presentation, antimicrobial resistance and toxicity question the outcome of transplantation. This retrospective study conducted at tertiary care apex transplant centre highlights colonization, clinical infection and antimicrobial resistance patterns in Renal Transplant Recipients (RTR). Materials and methods: Infection and antimicrobial resistance patterns in 130 RTR were studied. Clinico-demographic and transplant parameters were noted. Infection screening in the post transplant period along with antimicrobial susceptibility were used to analyze data in a post transplant time frame. Results and discussion: Culture positivity timeline was dominated by post surgical infections in the first week post transplant. Urinary infections followed by blood stream infections were noted. Infection profile included simultaneous polymicrobial, prolonged and widespread infections. Multi-resistant organisms producing beta lactamases and extended spectrum beta lactamases were isolated. Conclusion: Transplant recipients remain prone to bacterial infections with multi-resistant organisms which may persist due to immunosuppression, altered metabolism and toxicity, and contribute to nosocomial hazard. Infection control may be targeted at avoidance of donor derived infections, surgical complications, epidemiologic exposures, strengthening antimicrobial prophylaxis and anti-infection engineering. Antimicrobial stewardship, outbreak and epidemic preparedness should be ensured. DOI: http://dx.doi.org/10.3329/bjms.v14i1.16306 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.14-21